THE DEVELOPMENT OF CAREER CAPITAL THROUGH INTERNATIONAL CONSULTING WORK: A GERMAN CASE STUDY DURING THE COVID-19 PANDEMIC - Schmidt, Sarina Louisa (My University, 2021)
This study examines the influence of international consulting work on the development of consultant’s' career capital. The career capital can be outlined considering the three dimen-sions Knowing-Why, Knowing-How and Knowing-Whom. International work promotes the de-velopment of these dimensions. The first objective of this study is to investigate influencing factors on the development of career capital of individual employees of the case company. The second objective of this study is to identify changes in work processes in international consult-ing work and the resulting altered influence on career capital development due to the emerg-ing COVID-19 pandemic and the restrictions on work activities accompanying it. With the help of this study, it can be determined that international assignments include vari-ous drivers for the promoted and rapid development of career capital. All three components of career capital of the interviewed employees of the case company could be positively influ-enced by participating in international assignments in different project countries. The most important factors, which were essential for the development of all components, are the change of location and the cultural differences. These two factors entail further promoting effects for each element. They lead, for example, to a distinct corporate culture with accom-panying communication and work atmosphere differences that affect Knowing-Why and Knowing-How and Knowing-Whom, respectively. These effects were greatly diminished by the severe restrictions on travel necessary to combat the pandemic successfully. For the develop-ment of career capital, personal exposure to cultural differences enabled by business travel is a crucial factor that cannot be replicated or replaced by the use of digital communication media. The use of digital media can lead to communication problems, for example, due to time zone differences, but the experience of international project work in 2020 shows that such work can be carried out successfully without business trips. The results of this study can be used to complement existing studies in the area of career capi-tal and international work, mainly because of its relation to the pandemic. A qualitative case study is conducted in the course of this, combining an explanatory and exploratory purpose and using an abductive approach. Eight qualitative interviews with global careerists were con-ducted in order to extend the existing theory with the collected interview results. With the help of the interviews, the normal project management processes prior to the onset of the pandemic will be examined in order to determine an effect of international project work on the development of the career capital. Then, the current procedures will be considered with the perceived changes in terms of career capital development due to the changes in the im-plementation of projects abroad in 2020.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business